Immunosuppressant treatment reduces cocaine-induced behavioral sensitization in mice - de Oliveira, Gabriella Luciana; Machado da Silva, Maria Carolina; Gomes, Giovanni Freitas; Ribeiro, Roberta dos Santos; Cussat, Gabriela Reis; Fernandes, Rúbia Aparecida; Souza, Jorge Lucas Nascimento; Fernandes, Heliana de Barros; de Miranda, Aline Silva; Santos, Victor Rodrigues; Bueno, Lílian Lacerda; Vieira, Luciene Bruno; et al. (Frontiers in Pharmacology, 2026)
BackgroundNeuroinflammation plays fundamental, though still not fully understood, roles in the pathophysiology of substance use disorders, including cocaine addiction. Chronic cocaine exposure promotes neuroinflammatory signaling and synaptic alterations in brain regions involved in reward and memory, such as the striatum and hippocampus. Among the intracellular pathways regulating these processes, calcineurin, a calcium calmodulin-dependent phosphatase, has been implicated in synaptic plasticity, neuroinflammation, and psychiatric disorders. FK506 (tacrolimus), a calcineurin inhibitor and immunosuppressant drug used in the clinics, modulates neurotransmitter release, neurotrophic factor production, and microglial activity. However, its role in cocaine-induced neuroinflammatory and behavioral alterations remains poorly defined. In this context, we sought to evaluate whether FK506 alters the development of cocaine-induced behavioral, molecular, inflammatory, and structural alterations in C57Bl/6 male mice.MethodsMale C57Bl/6 mice (9–11 weeks) received FK506 (5 mg/kg, s.c.) or saline and were submitted to locomotor sensitization induced by repeated cocaine administration (15 mg/kg, i.p.). The hippocampus and striatum were collected for quantification of GDNF, TNF, IL-10, and IL-6 by ELISA, and for qPCR analyses of neuronal activity and plasticity related genes (PSD95, FosB, CREB, and ARC). Dendritic spine density was evaluated in the dentate gyrus and nucleus accumbens.ResultsIn male mice, FK506 attenuated cocaine-induced locomotor sensitization from the fourth day. The drug decreased hippocampal levels of GDNF, TNF-α, and IL-10 relative to the cocaine group, albeit no corresponding reductions were detected in the striatum. Consistent with this, FK506 neither altered plasticity- and activity-related gene expression nor reversed cocaine- induced dendritic spine loss.ConclusionTogether, these findings indicate that the immunosuppressant partially modulates cocaine’s effects, primarily by reducing the behavior sensitization and influencing specific neuroinflammatory and neurotrophic responses. Even without reversing structural or transcriptional alterations, the results suggest that immunomodulatory interventions may influence specific neurobiological adaptations to cocaine and warrant further investigation as potential therapeutic strategies.